2019
DOI: 10.26508/lsa.201800175
|View full text |Cite
|
Sign up to set email alerts
|

A junction coverage compatibility score to quantify the reliability of transcript abundance estimates and annotation catalogs

Abstract: Comparison of observed exon–exon junction counts to those predicted from estimated transcript abundances can identify genes with misannotated or misquantified transcripts.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
(64 reference statements)
2
15
0
Order By: Relevance
“…During the preparation of this manuscript, a preprint from Soneson et al . reported a similar observation and proposed the creation of a new index to flag such problematic genes 38 . While the current manuscript strongly emphasizes the role of 3’ UTRs in the emergence of estimation biases, we could pinpoint at least one example where 5’ UTRs play a similar role in the issue.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…During the preparation of this manuscript, a preprint from Soneson et al . reported a similar observation and proposed the creation of a new index to flag such problematic genes 38 . While the current manuscript strongly emphasizes the role of 3’ UTRs in the emergence of estimation biases, we could pinpoint at least one example where 5’ UTRs play a similar role in the issue.…”
Section: Discussionmentioning
confidence: 62%
“…The use of the JCC (Junction Coverage Compatibility) score introduced by Soneson et al . will be greatly useful to prevent misinterpretation of transcriptomics studies in the future but will tie quantifications to the results of computationally demanding alignment methods 38 . Improvement of current genomic annotations might ultimately offer an alternative as they will allow for the sole use of fast quantification algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the wide usage of gene or transcript expression data, we have seen improvement in probabilistic models of RNA-seq expression quantification [1][2][3][4], as well as characterization and evaluation of the errors of quantified expression [5][6][7]. However, there is an under-characterized type of estimation error which is due to the non-uniqueness of solutions to the probabilistic model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, external information about sequence similarity provides limited insight on how to improve the quantification models. Soneson et al [23] use a compatibility score of observed and predicted junction coverage to indicate genes with potential misquantification in its transcripts. With this anomaly score, it is possible to narrow down the misquantified transcripts by the anomalous splicing junctions.…”
Section: Introductionmentioning
confidence: 99%